Answer: A. One Solution
Explanation:
Simplifying
6 + -3x = 12 + -6x
Solving
6 + -3x = 12 + -6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '6x' to each side of the equation.
6 + -3x + 6x = 12 + -6x + 6x
Combine like terms: -3x + 6x = 3x
6 + 3x = 12 + -6x + 6x
Combine like terms: -6x + 6x = 0
6 + 3x = 12 + 0
6 + 3x = 12
Add '-6' to each side of the equation.
6 + -6 + 3x = 12 + -6
Combine like terms: 6 + -6 = 0
0 + 3x = 12 + -6
3x = 12 + -6
Combine like terms: 12 + -6 = 6
3x = 6
Divide each side by '3'.
x = 2
Simplifying
x = 2